Distribution of pharmaceutical compounds in coastal waters of the North Sea in March 2023 - Adenike Adenaya; Ruben Rios Quintero; Thorsten Brinkhoff; Pablo A Lara-Martín; Oliver Wurl; Mariana Ribas-Ribas (PANGAEA, 2023)
We investigated the occurrence, spatial, and vertical distributions of 63 pharmaceutical compounds and six artificial sweeteners from the sea surface microlayer (SML) to five different depths (0 cm, 20 cm, 50 cm, 100 cm, and 150 cm) of the corresponding underlying waters in four stations of the North Sea. One station is a coastal area (Jade Bay), one station is an estuary (Bremerhaven), and the other two stations (NS_7 and NS_8) are open coastal waters. We will refer to each environment with the name in brackets throughout this publication. We collected seawater samples vertically from these stations and analyzed them using ultra-performance liquid chromatography - triple quadrupole mass spectrometry in tandem with ionization spray (UPLC-QqQMS/MS) (Bruker EVOQ Elite system Bruker, USA) at the Department of Physical Chemistry, University of Cádiz.